Phrenic Nerve Reconstruction in Pediatric Diaphragm Paralysis: Outcomes and Techniques - Kaufman, Matthew R.; Lu, Charles; Staab, Victoriya; Bauer, Thomas (European Journal of Pediatric Surgery, 2025)
Symptomatic diaphragm paralysis in the pediatric patient is an uncommon condition. This study aims to evaluate the outcomes and technique of phrenic nerve reconstruction and its application to pediatric patients with unilateral and bilateral diaphragm paralysis at a single institution. The objective of this study is to demonstrate the application of a well-studied reconstructive technique in a population of patients not previously studied.A retrospective review of pediatric patients between 2012 and 2022 with symptomatic diaphragm paralysis treated with phrenic nerve reconstruction. Nine patients with a median age of 10 years were offered surgical treatment. The etiology of their paralysis included: birth trauma, congenital cervical anomaly, mediastinal neoplastic disease, cervical spinal cord injury, and acute flaccid myelitis. Measures of postoperative improvement include: fluoroscopic sniff testing, pulmonary function testing, electromyography/nerve conduction testing, ultrasound evaluation, and ventilator requirements.One hundred percent of patients with unilateral paralysis demonstrated improvement, defined as improvements in dyspnea, orthopnea, fatigability, and decreased respiratory infections. This was corroborated by sniff testing, pulmonary function testing, and electrodiagnostic evaluation. In 80% of patients, there was recovery of diaphragm excursion on the chest fluoroscopy, and a 10% or greater improvement in pulmonary spirometry (forced expiratory volume in 1 second, FEV1, and forced vital capacity, FVC) percent predicted values. In patients with bilateral diaphragm paralysis, 75% demonstrated improvement in sniff testing, ultrasound findings, and ventilator requirements. One of four patients with bilateral paralysis and chronic ventilator dependency did not improve. There were no postoperative complications defined as hematoma, wound infection, pleural effusion, pneumonia, sepsis, nerve injury, or hardware malfunction seen during follow-up.Phrenic nerve reconstruction in pediatric patients demonstrates potential as a safe and effective surgical option for symptomatic diaphragm paralysis. In patients with unilateral paralysis, this intervention consistently improved respiratory function. In patients with bilateral paralysis, the results were variable but showed promise in facilitating ventilator weaning when performed early. These findings underscore the importance of early surgical intervention. Larger, multicenter studies are needed to validate its long-term potential.
Keywords: diaphragm paralysis; phrenic nerve injury; diaphragm pacemaker; cervical tetraplegia; spinal cord injury